Enhancing Muslim Consumer Purchasing Decisions: The Impact of Product Quality, Price, Service Excellence, and Halal Certification - Amanda, Dinda Ardelia; Santosa, Perdana Wahyu (Research of Islamic Economics, 2024)
This research aims to determine the influence of Product Quality, Price, Service Quality, and Halal Certification on Muslim Consumer Purchasing Decisions at "Holland Bakery" in DKI Jakarta. The sample consists of 112 respondents who have purchased "Holland Bakery" products, selected through purposive sampling. Findings indicate that product quality and price positively and significantly affect purchasing decisions. However, service quality and Halal certification do not significantly impact purchasing decisions. From a managerial perspective, this research provides key insights for targeting the Muslim consumer market. It emphasizes that while product quality and competitive pricing are crucial, the presence of halal certification and superior service quality may not significantly sway purchasing decisions. Managers should focus on maintaining high product quality and competitive prices to meet the expectations of Muslim consumers, who prioritize these factors when making purchasing decisions.